New Evidence for Rural Anglian-Era and Early Medieval Settlement in the Lothians, at Burdiehouse, Edinburgh. Issue 1 (March 2021) - Maciver, Cathy; Paton, Kevin
Abstract : The results from archaeological fieldwork between 2014 and 2016 at Burdiehouse, Edinburgh, have revealed evidence of structures, pits and enclosures related to rural settlement and activity ranging across the Early Medieval period from the 7 th century AD up to the 12 th century AD. A suite of features included a truncated stone platform, remains of a small post-built building with a hearth and numerous pits, postholes and curvilinear ditches. In addition, a circular clay-lined kiln was recorded. Radiocarbon dating indicates that while the building and hearth, the stone platform and numerous of the pits, postholes and linear features related to activity between the 7 th and 10 th centuries AD, the kiln was a later feature, dated to the 12 th century AD. The evidence for rural Early Medieval settlement sites as identified at Burdiehouse is limited but recent work has emphasised how important they are for understanding everyday activity in this period.